2006
DOI: 10.1186/1471-2458-6-18
|View full text |Cite
|
Sign up to set email alerts
|

Changes in health related quality of life 3 months after an acute coronary syndrome

Abstract: Background: The aim of the study was to identify the changes in Health Related Quality of Life (HRQL) 3 months after discharge from hospital, in patients who have had an acute coronary episode, and to determine the clinical and sociodemographic variables that explain those changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
43
2
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 28 publications
10
43
2
7
Order By: Relevance
“…The age distribution of our study participants was similar to that reported in other studies investigating patients with CAD (10,(13)(14)(15)(16)22) . There was a greater proportion of men in our sample, which was also reported in other studies of HRQoL in patients with heart disease (10,(12)(13)(14)(15)(16)(17)(22)(23) .…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…The age distribution of our study participants was similar to that reported in other studies investigating patients with CAD (10,(13)(14)(15)(16)22) . There was a greater proportion of men in our sample, which was also reported in other studies of HRQoL in patients with heart disease (10,(12)(13)(14)(15)(16)(17)(22)(23) .…”
Section: Discussionsupporting
confidence: 72%
“…There was a greater proportion of men in our sample, which was also reported in other studies of HRQoL in patients with heart disease (10,(12)(13)(14)(15)(16)(17)(22)(23) .…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations